Low regeneration of lesions produced by coring in Orbicella faveolata - Rodríguez-Martínez,Rosa E.; Jordán-Garza,Adán Guillermo; Jordán-Dahlgren,Eric (PeerJ, 2016)
The extraction of tissue-skeleton cores from coral colonies is a common procedure to study diverse aspects of their biology, water quality or to obtain environmental proxies. Coral species preferred for such studies in Caribbean reefs belong to the genera Orbicella. The long term effects of coring in the coral colony are seldom evaluated and in many Caribbean countries this practice is not regulated. We monitored 50 lesions produced on Orbicella faveolata colonies by the extraction of two centimeter-diameter cores to determine if they were able to heal after a four year period. At the end of the study 4% of the lesions underwent full regeneration, 52% underwent partial regeneration, 14% suffered additional tissue loss but remained surrounded by live tissue, and 30% merged with dead areas of the colonies. Given the low capacity of Orbicella faveolata to regenerate tissue-skeleton lesions, studies that use coring should be regulated and mitigation actions, such as using less destructive techniques and remediation measures after extraction, should be conducted to facilitate tissue regeneration.
Keywords: Coral; Tissue-skeleton lesions; Tissue regeneration; Core sampling